(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This paper investigates the transformative role of empathy and emotional intelligence in educational leadership, focusing on the feminine dimension of management practices. In many post-Soviet educational systems, including Uzbekistan, leadership has long been defined through hierarchical and authoritarian traditions that prioritize control and discipline. However, a growing recognition of empathy, collaboration, and relationship-centered management highlights an alternative paradigm that redefines the essence of effective leadership. This study emphasizes how feminine leadership attributes such as active listening, inclusivity, and emotional awareness can enhance organizational culture, teacher motivation, and student engagement. It also examines how empathetic leadership practices contribute to building trust and innovation in educational settings.